Chemical profile and antioxidant activity of bidirectional metabolites from Tremella fuciformis and Acanthopanax trifoliatus as assessed using response surface methodology - Wu, Yuxiao; Liu, Yu; Wu, Jiayi; Ou, Kaiqi; Huang, Qian; Cao, Junxian; Duan, Tao; Zhou, Lin; Pan, Yufang (Frontiers in Nutrition, 2022)
Abstract: This study aimed to establish a bidirectional fermentation system using Tremella fuciformis (T. fuciformis) and Acanthopanax trifoliatus (A. trifoliatus) to promote the transformation and utilisation of the synthesised antioxidant metabolites from fermentation supernatant. The effect of fermentation conditions on the total phenolic content was investigated using response surface methodology in terms of three factors, including temperature (22–28°C), pH (6–8), and inoculum size (2–8%, v/v). The optimised fermentation parameters were: 28°C, pH 8, and an inoculum size of 2%, which led to a maximum total phenolic content of 314.79 ± 6.89 μg/mL in the fermentation supernatant after 24 h culture. The content of total flavonoids and polysaccharides reached 78.65 ± 0.82 μg/mL and 9358.08 ± 122.96 μg/mL, respectively. In addition, ABTS+, DPPH• and •OH clearance rates reached 95.09%, 88.85%, and 85.36% at 24 h under optimised conditions, respectively. The content of total phenolics, flavonoids and polysaccharides in the optimised fermentation supernatant of Tremella fuciformis–Acanthopanax trifoliatus increased by 0.88 ± 0.04, 0.09 ± 0.02 and 33.84 ± 1.85 times that of aqueous extracts from A. trifoliatus, respectively. Simultaneously, 0.30 ± 0.00, 0.26 ± 0.01 and 1.19 ± 0.12 times increase of antioxidant activity against ABTS+, DPPH• and •OH clearance rates were observed, respectively. Additionally, the metabolite composition changes caused by fermentation were analysed using ultra–high performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) based on untargeted metabolomics and the phytochemical profile of fermentation supernatant differentiated significantly based on unsupervised principal component analysis (PCA) during fermentation from 24 to 96 h. Furthermore, a significant increase in antioxidant phenolic and flavonoid compounds, such as ellagic acid, isochlorogenic acid B, vanillin, luteolin, kaempferol, myricetin, isorhamnetin, and (+)–gallocatechin, was observed after fermentation. Thus, these results indicated that the fermentation broth of T. fuciformis and A. trifoliatus had significant antioxidant activity, and may have potential application for health products such as functional beverages, cosmetics, and pharmaceutical raw materials.